2014
DOI: 10.3892/mmr.2014.3078
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin-3-glucoside isolated from mulberry fruits protects pancreatic β-cells against glucotoxicity-induced apoptosis

Abstract: The present study investigated the cytoprotective effects of cyanidin‑3‑glucoside (C3G), isolated from mulberry fruits, on the glucotoxicity‑induced apoptosis of pancreatic β‑cells to evaluate the antidiabetic effects of this compound. MIN6N pancreatic β‑cells were used to investigate the cytoprotective effects of C3G. In addition, the effects of C3G on the glucotoxicity‑induced apoptosis of pancreatic β‑cells was evaluated using MTT assay, immunofluorescent staining, flow cytometric and western blot analyses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 20 publications
3
19
1
Order By: Relevance
“…Studies have shown that cyanidin-3-glucoside isolated from mulberry fruit restrains high-glucose/H 2 O 2 -induced pancreatic β -cell death [30, 31]. In concurrence with previous studies, decreases in glucose consumption and uptake were observed in H 2 O 2 -induced HepG2 cells, meaning insulin resistance was formed.…”
Section: Discussionsupporting
confidence: 75%
“…Studies have shown that cyanidin-3-glucoside isolated from mulberry fruit restrains high-glucose/H 2 O 2 -induced pancreatic β -cell death [30, 31]. In concurrence with previous studies, decreases in glucose consumption and uptake were observed in H 2 O 2 -induced HepG2 cells, meaning insulin resistance was formed.…”
Section: Discussionsupporting
confidence: 75%
“…1,[5][6][7][8][9] Several studies reported that C3G protects against the adverse effects of UV-B radiation, controls the key aspects of tumorigenesis, inhibits the proliferation and induces the apoptosis of cancer cells, reduces oxidative stress, ghts H 2 O 2induced oxidative stress in human embryonic kidney (HEK-293) cells, and induces cell apoptosis and inhibits cell migration in TNF-a-challenged RASMCs in vitro. [10][11][12][13][14][15][16] Fratantonio found that C3G pretreatment effectively reverses the effects of PA on the PI3K/Akt axis and restores the eNOS expression and NO release. 17 Sivasinprasasn revealed that pretreatment with C3G inhibits the NF-kB signaling pathway.…”
Section: Introductionmentioning
confidence: 97%
“…Cyanidin is demonstrated to be beneficial against diabetes [4,5], cancer [6][7][8], and atherosclerosis [9]. In the central nervous system, recent investigations indicate that cyanidin showed potential protections against Alzheimer's disease and multiple sclerosis [10,11].…”
Section: Introductionmentioning
confidence: 99%